Sequence variants in the PTCH1 gene associate with spine bone mineral density and osteoporotic fractures - Unnur Styrkarsdottir (Nature Portfolio, 2016)
Bone mineral density (BMD) is the best predictor of osteoporotic fracture risk. Here, the authors perform a genome wide association study in Icelanders and people of European and East-Asian descent, and identify a new allele in intron 15 of the PTCH1gene that associates with reduced BMD.